Theoretical reflections on the use of oral history as a research methodology - Divino , Cláudia Roberta dos Anjos (Seven Editora, 2023)
The present text points out theoretical reflections about the basic concepts that surround our theme, such as the gender category, power relations throughout history and the silencing of women in historiography, so that it is evidenced how the history of women has been consolidated in the scientific field. In this perspective, oral history is configured as a collection procedure often used in historical research of education. In this case, we emphasize that this resource allows the researcher to use, in addition to written documents, oral documents as significant elements in the rescue of a story. Thus, the work was based on a bibliographic and conceptual analysis, employing authors such as Ricoeur (2007)), Alberti (2004), Portelli (2006) and Salvatici (2005), who address this theme in their descriptions. Henceforth this collection and analysis of the information based on the aforementioned authors were decisive and pertinent to the construction of this article and, as a result, it is verified that the genesis of women's history follows in the 1960s, concomitantly with the consolidation of oral history. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-050